Thermal Decomposition Kinetics of Fluorenone Thiosemicarbazone Complexes of Palladium(II) and Platinum(II) - Laly, S.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Thermogravimetric (TG), derivative thermogravimetric (DTG) and differential thermal analysis (DTA) curves of PdL2 and Pt(LH}2Cl2 (LH = fluorenone thiosemicarbazone) in air are studied. Mass loss considerations at the main decomposition stages indicate conversion of the Pd(II) and Pt(II) complexes to PdO and metallic platinum respectively. Mathematical analysis of TG data shows that first order kinetics are applicable in all cases. Kinetic parameters (energy and entropy of activation and preexponential factor) are reported.